A qualitative approach to investigate leakages in low-cost housing provision in Malaysia - Andrew Ebekozien,; Abdul-Rashid Abdul-Aziz,; Mastura Jaafar, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Over the years, Malaysian Government and housing developers have been providing low-cost housing (LCH) yet; shortage of homes for the low-income earners (LIEs) is high. Accessibility and affordability is a big issue in LCH scheme for the LIEs. Hence, this paper presents the qualitative approach to investigate LCH leakages in Malaysia. The purpose of this strategy is to explore the LCH leakage phenomenon from the participants. To achieve this, data were collected via in-depth oral interviews and validated via secondary sources. Thematic analysis was adopted and three themes emerged. Seven states and one territory in Malaysia were covered. From the findings, the participants agree on the high shortage of LCH. It is sadder that Malaysia is still experiencing LCH shortage after several years of LCH provision. Irregularities in auction of property, sales or rental within the moratorium period, non-compliance by housing developers with list of eligible buyers from the state government housing department, non-construction of LCH by developers because of unmerited waiver granted by state, politics in allocation of people’s housing program, allocation to non-eligible pro-government persons, and under-declaration of income by house-buyers were identified by the participants as the root causes of LCH leakages in Malaysia. Cumulative ruling for construction of LCH as against the conventional per project, joint task force comprises of planning office, land office, and state government housing department to monitor, engraved on LCH land title deed, functional open registration system (ORS), and central credit reference information system for eligibility check among others were recommended to mitigate LCH leakages.